Famous for thirty seconds - Kain, P. G. (Kain, P. G. Commercial breaks, 2012)
Brittany Rush expects the spotlight to shine on her again when she returns to New York after a year spent with her family in Hong Kong, but instead finds that she has changed from being a cute kid to watch out for to just another pretty girl waiting her turn.